Establishment of hairy root culture and its genetic transformation of Stephania tetrandra S. Moore for production of BIAs - Xiuhua Zhang; Junling Bu; Yujun Zhao; Qishuang Li; Xinyi Li; Ying Ma; Jinfu Tang; Jian Wang; Changjiangsheng Lai; Guanghong Cui; Juan Guo; Luqi Huang (Medicinal Plant Biology, 2023)
Metabolic engineering improvement of plants will play an essential role in future agriculture, but this largely depends on the establishment of genetic transformation. Stephania tetrandra S. Moore is a traditional Chinese medicine used for rheumatalgia that accumulates benzylisoquinoline alkaloids as its main active ingredients. Wild or farmed plants have remained the main source of these essential medicines, resulting in supply pressure due to the scarcity of wild plant resources and the slow growth rate in cultivation. Here, we constructed Agrobacterium rhizogenes (C58C1)-mediated hairy root culture and a co-transformation system in S. tetrandra to obtain a new source of bisbenzylisoquinoline alkaloids production. We show that the biomass of the hairy roots increased 10-fold, and the content of tetrandrine reached 8.382 ± 0.160 mg/g DW after 50 d of cultivation. In addition, overexpression of (R,S)-norcoclaurine 6-O-methyltransferase (6OMT) gene or treatment of hairy roots with methyl jasmonate (MJ) increased protoberberine alkaloid content. This work provides a method of obtaining hairy roots and a genetic transformation system for S. tetrandra, not only broadening the access to S. tetrandra resources, but also laying a foundation for further elucidation of the biosynthesis of tetrandrine and related alkaloids.